(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
The experiment was conducted to study the effect of mutagens (physical and chemical) on seed germination along with root and shoot lengths of two locally collected varieties of Brassica rapa denoted as variety-1 and variety-2 in in vitro condition. Seeds were treated with various concentrations of mutagenic agents; physical (gamma radiation), chemical (sodium azide) and combined (gamma radiation + sodium azide). The doses of gamma radiation were 100Gy and 200Gy, sodium azide concentrations were 100, 300 and 500ppm and for combination, 100Gy and 200Gy gamma irradiated seeds were further treated with 100, 300 and 500ppm sodium azide solution. After 7 days observation, 100% seed germination obtained from 100Gy gamma irradiated seeds of variety-1 and 500ppm sodium azide treated seeds of variety- 2. 100% seed germination was also found in 7 days in physical and chemical mutagen combinedly treated seeds of variety-1 from 100Gy gamma radiation + 100ppm sodium azide, 100Gy gamma radiation + 300ppm sodium azide and 200Gy gamma radiation + 100ppm sodium azide and in variety-2, from 100Gy gamma radiation + 500ppm sodium azide and 200Gy gamma radiation + 500ppm sodium azide. Maximum increased root length (avg. 3.8cm) was obtained from variety-1 combined treated (200Gy gamma radiation + 300ppm sodium azide) seeds and minimum decreased root length (avg. 1.0cm) was from variety-2 combined treated (100Gy gamma radiation + 100ppm sodium azide) seeds. Maximum increased shoot length (avg. 4.7cm) was obtained from variety-1 combined treated (200Gy gamma radiation + 100ppm sodium azide) seeds and minimum decreased shoot length (avg. 1.4cm) was obtained from variety-2 combined treated (100Gy gamma radiation + 100ppm sodium azide) seeds. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18274 Bangladesh J. Sci. Ind. Res. 48(4), 253-256, 2013